2018
DOI: 10.1101/508507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eco-evolutionary significance of 'loners'

Abstract: Loners, individuals out-of-sync with a coordinated majority, occur frequently in nature. 20 Are loners incidental byproducts of large-scale synchronization attempts or are they part of a 21 mosaic of life-history strategies? Here, we provide the first empirical evidence of naturally 22 occurring heritable variation in loner behavior, using the social amoeba Dictyostelium discoideum. 23 Moreover, we show that Dictyostelium loners-cells that do not join the multicellular life-stage-24 result from a dynamic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The two community-level metrics, mean coexistence time and species extinction 345 probabilities, provide important information about the diversity of the community at 346 different scales [36]. From a metapopulation perspective, each model realization 347 performed to obtain these observables can be related to the dynamics taking place 348 within distinct local regions, known as patches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The two community-level metrics, mean coexistence time and species extinction 345 probabilities, provide important information about the diversity of the community at 346 different scales [36]. From a metapopulation perspective, each model realization 347 performed to obtain these observables can be related to the dynamics taking place 348 within distinct local regions, known as patches.…”
mentioning
confidence: 99%
“…The fraction of patches occupied only by preys is given by 360 (1 − β)(1 − P (t)), and the fraction of patches in which overexploitation has caused prey 361 extinction is given by β(1 − P (t)). Hence, the mean coexistence time T and the prey 362 extinction probability β quantify the diversity of the community at different 363 spatiotemporal scales [33,36,38], that might serve as important guides for the design of 364 ecosystem management protocols [38,39]. 365 Since we were interested in studying whether the spatial coupling between mobility 366 and perception could lead to an eco-evolutionary feedback when both processes occur at 367 comparable time scales [14,15], we kept all the characteristic time scales of the system 368 fixed, except those related to diffusion and the evolutionary dynamics of perceptual 369 ranges.…”
mentioning
confidence: 99%
“…The action of selection on properties of isolated cells has been so far largely overlooked when considering the evolution of social traits, with the notable exception of the role of 'loner' cells [25,52,53]. Here, we showed that properties of isolated cells can be important not only in fluctuating environments, where different behavioural patterns are effective in hedging cells' bets in front of unpredictable selective pressures.…”
Section: Discussionmentioning
confidence: 75%